Answer:
We have laplace transform of any function is defined as
[tex]L[{f(t)}]=\int_{0}^{\infty }f(t)e^{-st}dt[/tex]
thus for [tex]f(t)=cos(at)[/tex]
[tex]L[cos(at)]=\int_{0}^{\infty }cos(at)e^{-st}dt[/tex]
Now integrating the given expression using the integration by parts principle we have
[tex]\int cos(at)e^{-st}dt=cos(at)\int e^{-st}dt-\int \frac{dcos(at)}{dt}\int (e^{-st}dt)dt\\\\=cos(at)\frac{e^{-st}}{-s}-(\int -asin(at)\frac{e^{-st}}{-s})\\\\-\frac{cos(at)e^{-st}}{s}-\frac{a}{s}\int sin(at)e^{-st}dt\\\\=-\frac{cos(at)e^{-st}}{s}-\frac{a}{s}(sin(at)\int e^{-st}dt-\int \frac{dsin(at)}{dt}\int (e^{-st}dt)dt\\\\=-\frac{cos(at)e^{-st}}{s}-\frac{a}{s}[(\frac{sin(at)e^{-st}}{-s})-\int acos(at)\frac{e^{-st}}{-s}[/tex]
Note that we get the first integral back in the RHS expression
Thus solving we have
[tex]I=-\frac{cos(at)e^{-st}}{s}+\frac{asin(at)e^{-st}}{s^{2}}+\frac{a}{s}I[/tex]
Solving for I we get
[tex]I=\frac{e^{-st}(-scos(at)+asin(at))}{s^{2}+a^{2}}[/tex]
now applying the limits we have
[tex]I=\frac{e^{-st}(-scos(at)+asin(at))}{s^{2}+a^{2}}|_{0}^{\infty }\\\\I=\frac{s}{s^{2}+a^{2}}(\because \lim_{t\rightarrow \infty}e^{-st}=0)[/tex]